Instruments for repairing the nets - Mumbai Archive Project Team (Jio Institute, 2024)
Net repair is done entirely manually, using simple tools like tasari and kathli. Tasari is a mending needle made of plastic, usually six inches long, around which the twine is wrapped. Kathli is a small knife used to cut the twine.